A review of the efficacy of atomoxetine in the treatment of attention-deficit hyperactivity disorder in children and adult patients with common comorbidities - Clemow DB (Dove Medical Press, 2017)
David B Clemow,1 Chris Bushe,2 Michele Mancini,3 Michael H Ossipov,4 Himanshu Upadhyaya1 1Eli Lilly and Company, Indianapolis, IN, USA; 2Eli Lilly, Windlesham, UK; 3Eli Lilly Italia S.p.A., Sesto Fiorentino, Italy; 4inVentiv Health Clinical, LLC, Blue Bell, PA, USA Abstract: Attention-deficit hyperactivity disorder (ADHD) is a common neuropsychiatric disorder that is often diagnosed during childhood, but has also increasingly been recognized to occur in adults. Importantly, up to 52% of children (including adolescents) and 87% of adults with ADHD also have a comorbid psychiatric disorder. The presence of a comorbid disorder has the potential to impact diagnosis and could affect treatment outcomes. Atomoxetine is a nonstimulant treatment for ADHD. Despite numerous published studies regarding efficacy of atomoxetine in the treatment of ADHD in patients with comorbid disorders, there is limited information about the impact of individual common comorbid disorders on the efficacy of atomoxetine for ADHD, especially with regard to adults. Moreover, a cumulative review and assessment of these studies has not been conducted. For this reason, we performed a literature review to find, identify, and cumulatively review clinical studies that examined the efficacy of atomoxetine in the treatment of patients with ADHD and comorbid psychiatric disorders. We found a total of 50 clinical studies (37 in children; 13 in adults) that examined the efficacy of atomoxetine in patients with ADHD and a comorbid disorder. The comorbidities that were studied in children or in adults included anxiety, depression, and substance use disorder. Overall, the presence of comorbidity did not adversely impact the efficacy of atomoxetine in treatment of ADHD symptoms in both patient populations. In the studies identified and assessed in this review, atomoxetine did not appear to exacerbate any of the comorbid conditions and could, therefore, be an important therapy choice for the treatment of ADHD in the presence of comorbid disorders. Keywords: comorbid psychiatric disorders, ADHD in children or adolescents, adult attention-deficit hyperactivity disorder, ADHD